Slavery bondage throughout history - Watkins, Richard Ross (Houghton Mifflin, 2001)
Traces the countless journeys and trials of slaves around the world and throughout time. Not only chronicles the terrible legacy of human oppression, he also champions those who fought against it and helped shape slave-free nations for future generations to inherit.
Includes bibliographical references (p. 126) and index
Keywords: Geschichte; Sklaverei; Slavery -- History; Slavery -- History -- Juvenile literature; Jugendsachbuch